The effectiveness of mainstream media in communicating government programme : a survey in Kg. Beringgis, Papar / Adie Made and Hazwanie Abd Rahim - Made, Adie; Abd Rahim, Hazwanie (2014)
Mainstream media has communicates many government information to public ever since before our country independent. Mainstream media play important role in Malaysia as it is the main medium used by government in communicating its programme to public. Besides that, government also has control over mainstream media in Malaysia. This is because government need strong medium to link them with the public. This research studies the effectiveness of mainstream media in communicating government programme. A random sample of 201 people who live in Beringgis, Papar will become our respondents in order to obtain answers for the questions, problem and issue in this research.